Pemungutan Pajak Negara dalam Perspektif Hukum Islam: Studi Komparasi Pendapat Imam Ibnu Ḥazm dan Imam al-Gazālī: State Tax Collection in Islamic Law Perspective: A Comparative Study of the Opinions of Imam Ibn Ḥazm and Imam al-Gazālī - Muhammad Yusram; Sayyid Tashdiq; Firmansyah Firmansyah; Azwar Azwar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study aims to examine and understand the views of Imam Ibn Ḥazm and Imam al-Ghazālī regarding the legality of state taxation in Islam and their relevance to the fiscal policies of modern states. The study employs a library research method using a descriptive qualitative approach combined with a normative juridical perspective. The analysis is conducted by exploring the methodological and argumentative differences between the two scholars and relating their views to the fiscal needs of contemporary states in establishing an equitable taxation system. The findings reveal that, first, Imam Ibn Ḥazm rejects the imposition of taxes beyond zakat due to the absence of explicit textual evidence in Islamic law, whereas Imam al-Ghazālī permits the collection of additional taxes under exceptional circumstances for the sake of public welfare (maṣlaḥah), provided that such taxation is just, proportional, and temporary. Second, the perspectives of these two scholars are complementary in nature: Ibn Ḥazm’s approach serves as a normative safeguard against the potential abuse of fiscal authority, while al-Ghazālī’s approach is more adaptable and applicable to addressing the fiscal demands of modern states. The integration of these perspectives may provide both a normative and ethical foundation for developing an Islamic taxation system that is legitimate, equitable, and contextually relevant. The implication of this study is that the maṣlaḥah-based approach can enrich the methodology of Islamic legal reasoning (istinbāṭ al-aḥkām) in addressing contemporary taxation issues. These findings underscore the importance of formulating fiscal policies that are fair, context-sensitive, and firmly grounded in the principles of Islamic law.